Digital Networked Information Society and Public Health: Problems and Promises of Networked Health Communication of Lay Publics. Issue 1 (2nd January 2018) - Kim, Jeong-Nam
ABSTRACT: This special issue of Health Communication compiles 10 articles to laud the promise and yet confront the problems in the digital networked information society related to public health. We present this anthology of symphony and cacophony of lay individuals' communicative actions in a digital networked information society. The collection of problems and promise of the new digital world may be a cornerstone joining two worlds—pre- and postdigital network society—and we hope this special issue will help better shape our future states of public health.